DicMath application with songs: A solution for overcoming misconceptions in mathematics story problems in elementary schools - Asyifa, Isyrak Yumna; Sutikno, Putri Yanuarita (Indonesian Journal of Science and Mathematics Education, 2025)
Mathematical word problems are an essential part of elementary school learning. However, many students develop misconceptions when solving them, highlighting the need for innovative solutions to enhance their understanding. This study aims to develop and evaluate the feasibility and effectiveness of the DicMath (Dictionary of Mathematics) application, which incorporates songs as a learning medium to address misconceptions in mathematical word problems. The application uses the Problem-Based Learning (PBL) model for third-grade elementary school students.   This research follows the Research and Development method using the ADDIE development model. Data analysis techniques include media feasibility tests, normality tests, t-tests, and N-Gain tests to assess the application's effectiveness. The findings indicate that the DicMath application, enhanced with song-based learning, was rated as 'highly feasible,' receiving a feasibility score of 92.6% from material experts and 95% from media experts. The N-Gain test results demonstrated a high effectiveness level on a small scale (0.7383) and a moderate effectiveness level on a large scale (0.6101). Therefore, the DicMath application with song integration is considered both feasible and effective in addressing students' misconceptions about mathematical word problems. This study contributes to developing interactive, technology-based learning tools that enhance students' understanding and support more effective elementary school learning.